Ответы и объяснения

Лучший Ответ!
2013-03-02T15:55:33+04:00

z^2-5+12i=0  z=a+bi  (a+bi)^2=a^2+2abi-b^2=a^2-b^2+2abi

a^2-b^2+2abi=5-12i

|a^2-b^2=5  |a=-6/b                |36-b^4-5b^2=0  |b^4+5b^2-36=0  |(b1)^2=9

|2ab=-12     |36/(b)^2-b^2=5   |a=-6/b               |a=-6/b                |(b2)^2=-4

                    |b#0                     |b#0                   |b#0                    |a=-6/b

|b1=3      |z1=-2+3i                     |z1=-2+3i

|b2=-3     |z2=2-3i                       |z2=2-3i

|b3=2i      |z3=3i+2ii=-2+3i

|b4=-2i     |z4=-3i-2ii=2-3i

|a1=-2

|a2=2

|a3=3i

|a4=-3i